1976
DOI: 10.1111/j.1365-2265.1976.tb01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic‐pituitary‐gonadal Relationships in Man From Birth to Puberty

Abstract: Gonadal function depends upon activities at various levels. Thus there is: (a) a central level (extra-hypothalamic, hypothalamic, and anterior pituitary); (b) an intermediate level (gonadal and plasma), and (c) a peripheral level consisting of the target organs to which the hormonal message is directed. These determine both the expression of gonadal function (physical, physiological, or psychological) and the feedback regulation of the secretion of gonadotrophins.(a) Central level (i) Extra-hypothalamic centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
49
1
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(55 citation statements)
references
References 101 publications
(103 reference statements)
4
49
1
1
Order By: Relevance
“…This could be due to differences in hormone levels according to different assay platforms (23). Nevertheless, the reported levels of T in the control infants in the two KS studies were much higher (4-20 nmol/l (5th-95th percentiles); (14, 15)) than reported by any other study (2,3,5,(24)(25)(26)(27)(28), including this study.…”
Section: Discussioncontrasting
confidence: 52%
“…This could be due to differences in hormone levels according to different assay platforms (23). Nevertheless, the reported levels of T in the control infants in the two KS studies were much higher (4-20 nmol/l (5th-95th percentiles); (14, 15)) than reported by any other study (2,3,5,(24)(25)(26)(27)(28), including this study.…”
Section: Discussioncontrasting
confidence: 52%
“…The latter levels decrease during the first postnatal week, but a prominent secondary peak appears before 3 months of age (1)(2)(3)(4)(5)(6). The low prepubertal levels of serum T are gradually reached toward the age of 12 months (1-6).…”
Section: Discussionmentioning
confidence: 87%
“…The testis tissue is clearly under increased gonadotropin support during months 1-3 of age, as demonstrated by measurements of circulating luteinizing hormone and follicle-stimulating hormone (2,4,6). The gonadotropin peak could be a result of decreased negative feedback from the testis, as reflected by the decreased bioactive fraction of circulating T. Experiments in rhesus monkeys show that the testicular negative feedback on gonadotropin secretion is functional in utero (1 3) and immediately after birth (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the 2nd half of fetal life, negative feedback becomes gradually established and this appears earlier in male fetuses than in females. During the perinatal phase, there is a further increase in circulating testosterone over the 1st 6 months of life (Forest et al, 1976). Circulating androgens, both testosterone and its primary metabolite, DHT, are synthesized and released from the testes during the perinatal period (Sokka and Huhtaniemi, 1995).…”
Section: Circulating Androgen Levels Increase Transiently During Devementioning
confidence: 99%